Resolution of the reaction sequence during the reduction of O2 by cytochrome oxidase. - Varotsis, C (1993)
Time-resolved resonance Raman spectroscopy has been used to study the reduction of dioxygen by the mitochondrial enzyme, cytochrome oxidase. In agreement with earlier reports, Fe(2+)-O2 and Fe(3+)-OH- are detected in the initial and final stages of the reaction, respectively. Two additional intermediates, a peroxy [Fe(3+)-O(-)-O-(H)] and a ferryl (Fe4+ = O), occur transiently. The peroxy species shows an oxygen-isotope-sensitive mode at 358 cm-1 that is assigned as the nu(Fe(3+)-O-) stretching vibration. Our kinetic analysis indicates that the peroxy species we detect occurs upon proton uptake from bulk solution; whether this species bridges to Cu(B) remains uncertain. For the ferryl, nu(Fe(4+) = O) is at 790 cm-1. In our time-resolved spectra, the 358 cm-1 mode appears prior to the 790 cm-1 vibration. By using kinetic parameters deduced from the time-resolved Raman work and from a variety of time-resolved optical studies from other laboratories, we have assigned rate constants to several steps in the linear reaction sequence proposed by G. T. Babcock and M. Wikström [(1992) Nature (London) 356, 301-309]. Simulations of this kinetic scheme provide insight into the temporal behavior of key intermediates in the O2 reduction process. A striking aspect of the reaction time course is that rapid O2-binding and trapping chemistry is followed by a progressive slowing down of succeeding steps in the process, which allows the various transient species to build up to concentrations sufficient for their detection by our time-resolved techniques. Our analysis indicates that this behavior reflects a mechanism in which conditions that allow efficient dioxygen bond cleavage are not inherent to the active site but are only established as the reaction proceeds. This catalytic strategy provides an effective means by which to couple the free energy available in late intermediates in the reduction reaction to the proton-pumping function of the enzyme.